Clinical Documentation Standards - Promise or Peril? - Lynn M. Nagle (Nursing Leadership, 2007)
Imagine a future of integrated clinical information systems that transcend the physical boundaries of clinical units, institutions and community care, providing nurses with comprehensive access to information and knowledge to support the delivery of care to individuals and families. Imagine not having to gather the same information repeatedly, ask the same questions over and over again, or struggle to assimilate information from multiple sources and informants. Better yet, as a person needing the services of the healthcare system, imagine not having to rely on memory for details of family health history or repeatedly provide the same information to numerous caregivers over the course of a single encounter (or multiple encounters) to satisfy the requirements of their specific data collection forms. The future lies in the electronic health record - but are we taking the right steps to get there? In particular, are we sufficiently challenging the status quo of the documentation structures associated with clinical information management?
Keywords: informatics, clinical information systems, clinical documentation standards, electronic health record